Survey on Cardiologists’ Perspectives on Cardiac Point-of-Care Ultrasounds (POCUS) - Linda Liu; Christine Chow; Cooper Kersey; Brandon Wiley; Jonathan Lindner; Andrew Pattock; Carlos Alviar; Sula Mazimba; Yoonsik Cho; Kavita Khaira; James Kirkpatrick; Younghoon Kwon (POCUS Journal, 2024)
Introduction: Cardiac point of care ultrasound (POCUS) has been used with increasing frequency. As a result of this trend, this study sought to characterize cardiologists’ perspectives on cardiac POCUS. Methods: An 18-question survey on demographics, cardiac POCUS clinical practice, education, and infrastructure was distributed by 16 academic medical centers. Likert scale responses were categorized into three groups: 1) “strongly agree” or “agree” 2) “strongly disagree” and “disagree” and 3) “neutral.” Results: Of the 140 survey responses collected from January to September 2021, 41% of respondents used cardiac POCUS more than twice in an inpatient week. Seventy-one percent of cardiologists believed that cardiac POCUS should be integrated more regularly into clinical practice and into cardiology fellowship education. Less than half of respondents (44%) reported easy access to POCUS devices, and more than half of respondents (56%) did not think there was appropriate institutional infrastructure to easily upload and document cardiac POCUS images (56%). Conclusions: Academic cardiologists had varying opinions on the use and impact of cardiac POCUS. However, most cardiologists believed that cardiac POCUS should be more incorporated within practice despite persisting infrastructure barriers.